Self-Management Embedded in Daily Activities: A Photoelicitation Focus Group Study among Persons with Spinal Cord Injury and Their Primary Caregivers in Bangladesh - Salma Begum; Yeasir A. Alve; Peter Bontje (Occupational Therapy International)
Purpose. This study explored how community-dwelling persons with spinal cord injury (SCI) and their primary caregivers execute self-management strategies in daily activities. These strategies were mapped to a preexisting self-management framework. Methods. Photoelicitation focus group discussions were conducted among 14 adults with SCI and their primary caregivers (in two groups). Moreover, a constant comparative framework was used to analyze the data. Results. This study identified nine groups of self-management strategies, some of which could not be categorized under the three main self-management components generally accepted in the literature. Accordingly, a new component is proposed based off of this analysis, entitled management of social complexities, which includes crucial strategies such as (1) relocating to another environment, (2) behaving in an assertive manner, and (3) advocating for social change. Conclusion. The results show that self-management, traditionally described as medical, emotional, and role management, should also include the management of social complexities. The identified strategies could be considered in the development of self-management enhancement programs in lower-middle-income countries.